Effects of a modified ball on the mechanics of selected water polo skills in novice children - Pittuck, D. E. (Swimming III. Proceedings of the Third International Symposium of Biomechanics in Swimming, University of Alberta, Edmonton, Canada, 1979)
Although more and more children are exposed to water polo each year, relatively few of them remain involved in the sport. Because of the unique demands on the player`s skill, this sport can be extremely frustrating to the novice. A major source of this frustration seems to be an inability to acquire ball-handling skills using the large, regulation-sized ball. A plausible solution could be to start with a smaller ball. This approach is supported by other researchers (Egstrom, Logan, and Wallis, 1960; Wright, 1969), who investigated learning skills with modified equipment. Egstrom, Logan, and Wallis showed (1960) that subjects who practiced a throwing skill with a light ball were better able to transfer the skill to a heavier ball than those who practiced with the heavier ball. Morris (1976) indicated that, by changing the mechanical efficiency of a movement pattern, such as throwing, a child`s total movement capability could be changed. These changes could be positive if improved mechanical efficiency were obtained by modifying the size, weight, texture, or speed of an implement in a throwing skill. Consequently, the hypothesis that children would learn the proper skill mechanics earlier in training using modified equipment was proposed. More specifically, the purpose of this study was to determine the effects of an experimental ball on the mechanics of the drive-in overhand water polo shot in novice children. A subproblem was to determine whether or not the transfer of skill mechanics was facilitated by the modified equipment. To investigate the hypothesis that modified equipment would be beneficial, as suggested by Morris (1976), a biomechanical approach was undertaken.